2000
DOI: 10.1046/j.1464-410x.2000.00835.x
|View full text |Cite
|
Sign up to set email alerts
|

Inactive free : total prostate specific antigen ratios in ejaculate from men with suspected and known prostate cancer, compared with young control men

Abstract: Inactive free : total prostate speci®c antigen ratios in ejaculate from men with suspected and known prostate cancer, compared with young control men Objective To measure free : total prostate speci®c antigen (PSA) ratios in ejaculate from men with suspected and known prostate cancer, and in young control men, to determine if this ratio might be useful in discriminating benign from malignant prostatic conditions. Patients, subjects and methods Forty-seven men with prostate cancer (positive biopsies), 52 men wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…However, measuring serum levels of PSA under normal conditions, i.e., in healthy men is probably not the optimal way of assessing prostate gland function. In men without prostatic disease, the levels of the PSA in seminal fluid is about 106 times higher than in serum [18], the former being the natural way of excretion of this enzyme. Measuring seminal amounts of PSA is thus a better approach to evaluate androgen dependent prostate function.…”
Section: Introductionmentioning
confidence: 94%
“…However, measuring serum levels of PSA under normal conditions, i.e., in healthy men is probably not the optimal way of assessing prostate gland function. In men without prostatic disease, the levels of the PSA in seminal fluid is about 106 times higher than in serum [18], the former being the natural way of excretion of this enzyme. Measuring seminal amounts of PSA is thus a better approach to evaluate androgen dependent prostate function.…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, SP donation is completely non-invasive avoiding the discomfort and possible concerns associated with prostate massage necessary to obtain post-massage urine. Previously, we reported that the inactive free:total PSA ratios in SP from men with suspected PCa did not distinguish between those harboring malignant as opposed to benign disease [16]. The present study was designed to assess changes in Dkk-3 levels in SP and its potential for discriminating benign from malignant prostatic conditions in patients who were to undergo TRUS-guided biopsy due to elevated serum PSA (> 4 ng/mL) and/or abnormal DRE.…”
Section: Discussionmentioning
confidence: 95%
“…Samples were layered over 10 mL of 64% isotonic Percoll (Amersham Biosciences) and centrifuged at 2200 rpm for 30 min at 4°C. The ejaculate supernatants (SP) were removed, aliquoted and stored at -70°C until further processing (as reported previously [16,17]). The study had the approval of the ethics committees of the RBWH and University of Queensland.…”
Section: Methodsmentioning
confidence: 99%
“…The major seminal fluid protein of prostatic origin is PSA or KLK3 at a concentration of 0.5 to 3.0 mg/mL. [9][10][11][12][13] In contrast to serum, PSA in seminal fluid is predominantly (95%) uncomplexed. 13 The main forms of free PSA (those not complexed; that is, not bound to inhibitors) in seminal fluid include the mature form that is capable of enzymatic activity, and internally clipped or N-terminally truncated forms that are enzymatically inactive.…”
Section: Prostate-specific Antigen or Klk3mentioning
confidence: 99%
“…19,48 KLK5 can also complex with a 1 -antitrypsin and a 2 -macroglobulin in serum and ascites fluid. 49 In contrast to PSA, all of these proteases ( KLKs 1,2,4,5,6,8,10,11,13,and 14) are trypsin-like, with a preference to cleave protein substrates after an arginine or lysine residue (reviewed by Clements et al, 5 Rittenhouse et al, 13 and Borgono. 50 Because they are secreted as inactive zymogens and most (except for KLK4) require cleavage of their propeptide after lysine (KLK6, 8,13,14) or arginine (KLKs 1, 2, 3, 5, 10, 11), the presence of several different KLK proteases in the seminal fluid suggests that a tightly regulated KLK enzymatic cascade may exist.…”
Section: Prostate-specific Antigen or Klk3mentioning
confidence: 99%